Onkareshwar Mahadev Temple - Ghosh, Ayan (2023)
In front of Walkeshwar Temple is the Onkareshwar Mahadeo Temple, commissioned by Mathuradas Dwarkadas. This temple has a squat deepstambha adjoining it. The temple is dedicated to Lord Shiva, represented by a stone lingam that is fabled to be swayambhu (self-manifesting). Next to the temple stands an old banyan tree.